Kuma-Kuma Chan's travels - Takahashi, Kazue, 1971- (Kuma-Kuma Chan, 2017)
In the third book in the Kuma-Kuma Chan series, Kuma-Kuma Chan flies off to a South Sea isle where he lies in the sun and drifts into a lazy snooze. He climbs to the summit of a mountain and views the sunrise while drinking a cup of coffee. He even travels back to before he was born to find out what kind of animal he was in a previous life. Instead of physically setting out for one place or another, Kuma-Kuma Chan travels freely all over the world - inside his head.--Publisher.